2018
DOI: 10.1016/j.stem.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Fixation and Spread of Somatic Mutations in Adult Human Colonic Epithelium

Abstract: SummaryWe investigated the means and timing by which mutations become fixed in the human colonic epithelium by visualizing somatic clones and mathematical inference. Fixation requires two sequential steps. First, one of approximately seven active stem cells residing within each colonic crypt has to be mutated. Second, the mutated stem cell has to replace neighbors to populate the entire crypt in a process that takes several years. Subsequent clonal expansion due to crypt fission is infrequent for neutral mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 39 publications
8
123
0
Order By: Relevance
“…Measuring the numbers of stem cells per crypt is difficult because the experimental fate marker approaches used in mice (8) are impractical. However, other approaches that measure somatic alterations indicate that human crypts also contain multiple stem cells (12,1620). A recent study indicated that certain selective mutations can increase colon crypt fission (from one to two crypts) above a baseline rate of ~0.7% per year, which can further favor progression (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring the numbers of stem cells per crypt is difficult because the experimental fate marker approaches used in mice (8) are impractical. However, other approaches that measure somatic alterations indicate that human crypts also contain multiple stem cells (12,1620). A recent study indicated that certain selective mutations can increase colon crypt fission (from one to two crypts) above a baseline rate of ~0.7% per year, which can further favor progression (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, other approaches that measure somatic alterations indicate that human crypts also contain multiple stem cells (12,1620). A recent study indicated that certain selective mutations can increase colon crypt fission (from one to two crypts) above a baseline rate of ~0.7% per year, which can further favor progression (20). Very few studies have compared human SI and colon crypts, and a study with passenger methylation indicated that human SI and colon crypts contain multiple mitotic stem cells that divide at similar rates (21).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a fast self-renewing tissue like the intestinal epithelium within which the cell-of-origin for common tumours is likely to be a stem cell 23 , the highly compartmentalized stem-cell niche might pose an effective barrier to oncogenic field effects. The intestinal epithelium is one of the most proliferative tissues subject to a high mutagenic burden and it has been broadly studied both mathematically 24,25 and experimentally 23,26,27 . A small group of adult stem cells reside within the colonic crypt and maintain the homeostasis of the villi lining the intestine 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelium is one of the most proliferative tissues subject to a high mutagenic burden and it has been broadly studied both mathematically 24,25 and experimentally 23,26,27 . A small group of adult stem cells reside within the colonic crypt and maintain the homeostasis of the villi lining the intestine 23 . Within the crypt and the villus, the balance between proliferation and differentiation is maintained by a complex network of signals (e.g., WNT, NOTCH, BMP, and EGF) generated by specialized Paneth cells within the crypt and cells within mesenchyme lining the crypt 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation